MASYARAKAT PETANI KAMPUNG PARIT BUGIS DESA BINTAN BUYU KABUPATEN BINTAN - Prasetyo, Adi Gilang; Wahyuni, Sri; Solina, Emmy (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research aimed to find out how the rice farming community of Kampung Parit Bugis is making efforts to maintain their profession. The method used in this study is a qualitative method with a descriptive approach with interviews, observations, and documentation. The interviews were special interviews with rice farmers only, after which the information obtained in the field was interpreted using descriptive analysis techniques. After research, it was found that the low level of education and lack of job opportunities allowed farmers to survive and continue to practice their profession. The rice farmer's job has been passed down through generations, and their expertise is only in farming. The efforts of rice farmers in Parit Bugis Village to survive are by making savings by minimizing household expenses, optimizing existing resources, doing other work to find an extra income outside of their work, and taking advantage of family members where they take advantage of their family members. to be able to help in their daily needs and to build networks with the formation of farmers' groups to strengthen and maintain the continuity of their profession